Implementing Dementia Care Mapping in Dementia Care: A Narrative Realist Literature Review - Andreia Fonseca de Paiva; Ana Barbosa; Lindsey Collins; Siobhan Reilly (Journal of Long-Term Care)
Context: Dementia care mapping (DCM) is a multicomponent intervention to deliver person-centred care (PCC) for people with dementia. While the research has demonstrated the positive impact of DCM in care homes, more needs to be understood about the contexts and underlying mechanisms that may affect its implementation and uptake.